Slovenski roman po sledovih evropskega naturalizma - Gacoin-Marks, Florence (Jezik in slovstvo, 2004)
Kapitanovi is written as a novel on three levels: on a family level, a social level and the level of the individual. Following the example of the naturalist novel, this novel foregrounds the decay of a family in which the iterpersonal effects of a relationship between an individual and the environment are clearly achieved. In the thirties of the previous century, Slovenia had not yet been saturated with naturalist novel writing. A great naturalist novel, as developed in some other literatures at the end of the 19th century, is almost a new genre within Slvoene novel writing. From both the thematis, as well as the structual and narrative viewpoint Kapitanovi is placed among the earliest naturlaist novels: the facing of an individual and their inborn traits with the envirinment, the portrayal of decay, writing the story as "a slice of life" and the extensive use of a personal narrator, are all features which make this novel an undoubtedly late, but complete assertion of naturalism.
Keywords: Kranjec, Miško, 1908-1983; Slovene literature; slovenska književnost; naturalizem; Kranjec, Miško: Kapitanovi; literarne študije